Thoracic empyema: clinical course and management in Trivandrum Medical College - P. S., Sony; C. V., Vinu; J., Suresh Kumar; Lal, Kishore (International Journal of Research in Medical Sciences, 2021)
Background: The incidence of empyema thoracis among adults is increasing steadily. It may be primary empyema (pleural infection developing without pneumonia) or secondary empyema. The common cause of secondary empyema being- community acquired pneumonia or hospital acquired pneumonia, empyema due to iatrogenic causes, secondary to trauma etc. With advancement in science and technology, early recognition of empyema in patients with symptoms is now possible. But the treatment guidelines are not unified so that each physician may treat this condition in a different way without referring to higher concerned specialties making it complicated. The objective of this study was to determine the clinical profile of thoracic empyema in Trivandrum Medical College a tertiary care centre in South Kerala. Methods: A total of 56 patients with empyema admitted to Government Medical College, Trivandrum, Kerala in 2018-2019 were reviewed retrospectively. The demographic details, clinical presentation, etiology, microbiological findings, and management were recorded in a planned proforma, and analysis was done. Results: The mean age was 49.1 years with peak incidence seen in 40-60 years of age. The male to female ratio was 4.6:1.0 and right pleura was more involved than left pleura. Risk factors were diabetes mellitus, chronic obstructive pulmonary disease, pulmonary tuberculosis, and smoking. Etiology of thoracic empyema was infective in 78.6% cases and traumatic in 21.4% cases. Only two cultures showed gram positive aerobe, rest of the culture was sterile. Only a few cases resolved with medical management. Decortication was needed for 52 patients (82.1%). Conclusions: A unified protocol need to be formulated and followed up in all centres for the management of empyema before its evolution and thus reducing the incidence of empyema and its associated complications.